Correction: Iron-catalyzed para-selective C–H silylation of benzamide derivatives with chlorosilanes. Issue 11 (9th April 2021) - Liu, Pei; Hao, Na; Yang, Dong; Wan, Lingyun; Wang, Tianyi; Zhang, Tao; Zhou, Rui; Cong, Xuefeng; Kong, Jie
Abstract : Correction for 'Iron-catalyzed para -selective C–H silylation of benzamide derivatives with chlorosilanes' by Pei Liu et al., Org. Chem. Front., 2021, DOI: ; 10.1039/d1qo00243k .